ЕФЕКТ КАВІТАЦІЇ ТА ЙОГО ЗАСТОСУВАННЯ ПРИ ОЧИЩЕННІ СТІЧНИХ ВОД ОБ’ЄКТІВ ТЕПЛОЕНЕРГЕТИКИ, ПРОМИСЛОВОСТІ, ПОБУТУ І СІЛЬСЬКОГО ГОСПОДАРСТВА - Obodovych, O.M.; Sydorenko, V.V.; Tselen, B. Y.; Stepanova, O.E. (Institute of Engineering Thermophysics of NAS of Ukraine, 2023)
Modern requirements for wastewater discharges set strict limits on the residual content of reagents used to disinfect liquids, the content of harmful and dangerous substances. In this regard, there is growing interest in reagent-free methods of processing liquid media. Reagent-free cleaning and disinfection methods do not pollute the natural environment with chemicals, do not have a harmful or irritating effect on the human body when in contact with purified water and other liquids. Currently, new ecological methods of decontamination of liquids due to their physical processing and reduction of the number of chemical reagents used for disinfection are promising. Such methods include ultraviolet irradiation, electric discharge, cavitation treatment and other methods of physical impact on the liquid. When comparing different decontamination methods, cavitation is an inexpensive method of liquid treatment. The use of cavitation disinfection in animal husbandry is at the research stage. When using livestock wastewater in agriculture, there is concern about the possibility of spreading helminths, so new methods of cleaning and disinfecting livestock effluents (as well as other types of wastewater) by cavitation method are needed for study. The purpose of the work is to conduct a survey to analyze the advantages and disadvantages of cavitation treatment of wastewater of various origins. Cavitation is a means of local concentration of low-density energy into a high-density energy flow associated with pulsations and slamming of cavitation bubbles. The energy released in the process of bubble collapse is sufficient for excitation, ionization and dissociation of water molecules, gases and substances with high vapor elasticity inside the cavitation cavity. Comparison of wastewater treatment data and cavitation number values allows us to conclude that cavitation directly affects the effectiveness of bactericidal treatment in hydrodynamic equipment. Cavitation treatment of wastewater with the introduction of a small amount of oxidizer (sodium hypochlorite) gives a synergistic effect and allows to reduce several times the amount of chemical reagents used for disinfection of wastewater. The proposed modern technical solutions for wastewater treatment of thermal power facilities must meet a number of requirements, namely, be energy-resource-saving, environmentally safe, economically feasible and at the same time highly efficient. The technology for cleaning wastewater generated at thermal power plants containing petroleum products and biological organisms, which is based on cavitation, meets the specified requirements. Complex problems of hydrodynamic influence on multicomponent liquid media are successfully solved on the basis of the method of discrete-pulse energy input – a fundamentally new method of intensification of hydrodynamic and heat-mass exchange processes. The principle of discrete-pulse energy input and transformation (DPEI) was proposed in as a generalizing method of directed, local and intensive use of concentrated energy in liquid dispersed systems. To intensify the process of aeration and mass transfer in the technology of biological wastewater treatment, a rotary-type aerator-oxidizer was created at the IET of the National Academy of Sciences. The use of a rotary-type aerator-oxidizer for wastewater treatment allows to intensify the mass transfer at the gas-liquid phase interface and to make the necessary content of dissolved oxygen in the treated medium constant. This is one of the most important factors in the intensification of the process of biological wastewater treatment. In addition, energy costs for aeration are 20 % less, compared to other analogues.